Response to Aguilar et al.’s (2015) critique of Ollerton et al. (2009) - Nickolas M. Waser; Jeff Ollerton; Mary V Price (Journal of Pollination Ecology, 2015)
In their response to Ollerton et al.’s (2015) cautions about methods used by Rosas-Guerrero et al. (2014) to test the pollination syndromes, Aguilar et al. (2015) criticize an earlier paper by Ollerton et al. (2009).  Here we respond to their concerns.